(untitled) (Bangladesh Journal of Animal Science, 2022)
The study was conducted to identify the socio-economic status and problems faced by the Sonali farmers at Wazirpur Upazila in Barishal District. A total of 90 respondents from 9 unions were selected randomly for primary data collection. The farmers and their farming were evaluated through the analysis of data collected in a pre-structured questionnaire. This study revealed that a maximum portion of the farmers were middle-aged (52.2%), male (92.2%), and had a secondary level of education (54.4%). Most farmers had medium-sized farm (38.9%) and invested their own capital in farming (54.9%). Although major farmers had low experience in Sonali chicken farming, they had high management skills (63.9%). In terms of occupation, the highest percentage of farmers (38.9%) had a conjugated occupation of poultry and crop. Most of the farmers had their own tube-well (74.7%) and use sanitary latrine (71.1%). Nevertheless, only 17% of the farmers had good health condition. About 49% of the farmers had only one chicken house, and 87.8% followed the floor system for rearing Sonali chicken. Surprisingly, all the farms followed an all-in-all-out marketing system for Sonali chicken. Most of the farmers (96.7%) vaccinated their poultry birds and added coccidiostat (73.3%) and vitamin mineral premix (94.4%) to the feed. A major portion of the farmers identified the irregular fluctuation in the market price of feeds (95.6%) and day-old chicks (93.3%) as severe problem, followed by high price of feed but low price of meat (87.8%). A disorganized marketing channel was the next major problem faced by the poultry farmers (83.3%). Taken together, the Sonali farmers of Barishal were middle-aged; poorly educated, and invested their own capital for farming, and they faced a variety of challenges during farming and marketing their chickens. To enhance Sonali farmers’ socio-economic conditions and alleviate their problems, the government should take appropriate steps to provide finance and farm-based training, including modern animal husbandry practices. Bangladesh Journal of Animal Science. 2022. 51 (1): 1-11